Establishment of Z Score Reference of Growth Parameters for Egyptian School Children and Adolescents Aged From 5 to 19 Years: A Cross Sectional Study - El Shafie, Ali M.; El-Gendy, Fady M.; Allahony, Dalia M.; Omar, Zein A.; Samir, Mohamed A.; El-Bazzar, Ahmed N.; Abd El-Fattah, Mohamed A.; Abdel Monsef, Amir A.; Kairallah, Amir M.; Raafet, Hythem M.; Baza, Ghada M.; Salah, Amany G.; et al. (Frontiers in Pediatrics, 2020)
Background: Growth charts are an important method for evaluating a child's health, nutrition and development. Objective: To establish Lambda – Mu- Sigma (LMS) and Z score references for assessment of growth and nutrition in Egyptian school children and adolescents. Methods: A total of 34,822 Egyptian school children and adolescents from 5years to 19 years were enrolled in a cross sectional randomized study from December 2017 to November 2019 to create LMS and Z score references for weight, height and body mass index (BMI) corresponding to ages. They were selected from different districts in Egypt. Apparent Healthy children with good nutritional history and not suffering from any chronic diseases were included in the study. Results: Egyptian children of both sexes (54.3% boys and 45.7 % girls) from 5 years to 19 years old were studied. Then LMS and Z scores for weight for age, height for age, BMI for age of both sexes were represented in detailed tables and graphs. There was no statistically significant difference between the Egyptian Z score charts and the reference values of WHO for weight, height and BMI corresponding to age (P>0.05). Conclusion: This is the first reference for growth and nutritional assessment in Egyptian school children and adolescents, this tool is essential for healthcare and research. In case of absence of these local charts, we recommend to use the WHO references values rather than other local charts.